Time of arrival estimation with music under impulsive noise - Hacıoğlu, İsa. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
With the emergence of micro and nano technologies, the context-aware wirelesscommunications applications have been spreading. Especially, location-awareness hasgained significance recently. The TOA estimation have been chosen by many wireless communications tech-nologies such as GSM, and GPS as a ranging metric for locating their subscribers. Oncethe TOA is estimated accurately, the distance between the transmitter and receiver isreadily obtained. The TOA is estimated from the first arriving signal component. If the first multipath component is not detectable, the accuracy of the localization schemeis threatened.The environmental noise is another significant factor that a®ects the performanceof the TOA estimator. Although most wireless communication researches assume that noise in the environment has Gaussian distribution, it has been shown that manyreal-world noise signals have impulsive nature which cannot be modelled by Gaussiandistribution. Instead, the stable distributions are used to model impulsive signals.The super-resolution FLOM-MUSIC method is proposed to obtain the delay characteristics of indoor channels under impulsive noise, and the performance comparisonbetween the FLOM-MUSIC and the traditional SOS-MUSIC is done. The improvedperformance with FLOM-MUSIC TOA estimator under impulsive noise is shown viasimulations.
Keywords: Signal processing.; Wireless communication systems -- Location.